Developing curriculum for the “Information technology” study programme - Soleša, Dragan (Array, 2012)
The paper analyzes the curriculum in the field of computing according to the timeline, and the latest trends in this area. Also, the paper presents the process of developing a new program “Information technology” in the Republic of Serbia. Plan and program of new study program “Information technology” the authors created according to the standards and programs “Computing Curricula 2005” and “Information Technology 2008”, internationally recognized professional organization, “IEEE - Computer Society of the Institute for Electrical and Electronic Engineers” in cooperation with the Association “ACM - Association for Computing Machinery” as well as international standards for the strategic direction of study programs in the field of computing.